Is Silver the Ultimate Antimicrobial Bullet? - Raymond J Turner (MDPI AG, 2018)
The use of metal compounds as antimicrobial agents has been around since antiquity, only to be replaced by the introduction of organic antibiotics and antiseptics in the mid-20th century. [...]